"The Book of the Chilean Huaso". The Institute of Information of Peasant and Mobilizations of Peasant (1939-1943) - Acevedo, Nicolás (Revista de Historia Social y de las Mentalidades, 2024)
"The following article discusses the work of the institute of peasant information, an organization created in the government of Pedro Aguirre Cerda, through the publication called The Book of Chilean Huaso what was destined to education and acculturation of farmers in the central zone. Our hypothesis is that the Popular Front government made a patronizing agricultural policy, annulling the union not only by repressive means, but also through an educational and cultural strategy that promoted modernization in the field, without breaking with the harmony in relations between capital and labor. On the other hand, by analyzing letters to the institute of information of peasant, we argue that the reception of the peasant masses often had the character of denunciation or required union advice, which the government institution not realized in its publications, but if they were derived other institutional bodies".
Keywords: Popular Front; Paternalism; Institute of Information of Peasant; The Book of Chilean Huaso